Peningkatan Hasil Belajar Siswa melalui Model PBL pada Materi Pecahan Sederhana Kelas III SDN 001 Barong Tongkok - Hartono Hartono; Yenny Suzana (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to improve student learning outcomes in Mathematics, especially simple fractions, through the application of the Problem Based Learning learning model. The background of this study is based on the need for an effective learning approach and encourage active student participation in learning simple fractions. The Problem Based Learning learning model is one of the learning approaches used to improve learning outcomes in Mathematics. This study applies the Problem Based Learning learning model to grade III students at SDN 001 Barong Tongkok in the 2024/2025 academic year. The study method used in this study is Classroom Action Research. Classroom action studies are applied through two cycles. Each cycle consists of four processes that are applied sequentially, namely planning, acting, observing, and reflecting. The class that is the subject of this study is grade I students with a total of 21 people. In the initial conditions, the average student score was 62.25. After implementing the first cycle, where the teacher applied the learning practice, the results obtained were that in cycle I, the average class score increased to 67.25, and in cycle II, the average score increased to 77.75. Through the action study applied through two cycles, a significant increase was obtained. Thus, it can be concluded that the Problem Based Learning learning model is effective in improving Mathematics learning outcomes in simple fractions in class III at SDN 001 Barong Tongkok